Fracture resistance of endodontically treated teeth, restored with two post-core systems in different post space diameters (in vitro study) - Kholoud B. Saad; Samir I. Bakry; Rewaa G. AboElhassan (BMC, 2023)
Abstract Background Fracture resistance of post-core restoration depends on the design of the post, post diameter, post length, the type of adhesive cement used along with material of the core. Despite the different studies concerning the effect of post space diameter on the fracture resistance of endodontically treated teeth, more information regarding fracture resistance and the effect of different post space systems/materials and diameters is required. Aim of the study This study aimed to evaluate fracture resistance of endodontically treated teeth, restored with two post-core systems in different post space diameters. Materials and methods Twenty freshly extracted maxillary central incisors were collected for this study. They were randomly divided into four groups according to intracanal post and its diameter. Group GN (glass-fiber post of 10-mm length and 1.3-mm diameter with composite core), group GW (glass-fiber post of 10-mm length and 1.75-mm diameter with composite core), group ZN (custom-made zirconia one-piece post-core of 10-mm length and 1.3-mm diameter) and group ZW(custom-made zirconia one-piece post-core of 10-mm length and 1.75-mm diameter). Fracture resistance for all samples was evaluated using the universal testing machine under a static load. The data was collected and statistically analyzed using One-Way ANOVA test. Modes of failure were assessed using stereomicroscope for each group. Results The highest mean fracture resistance was recorded in group GW (638.7 ± 285.1 N), followed by group ZW (598.5 ± 127.6 N), then GN group (442.8 ± 65.38 N). The lowest mean fracture resistance was recorded in group ZN (435.3 ± 117.3 N). One-Way ANOVA test revealed that there was no statistically significant difference in fracture resistance values among the groups. Conclusion Post space diameter had an impact over the fracture resistance of endodontically treated teeth. Modulus of elasticity of post material had a major effect on the fracture resistance and mode of failure along with the restorability of the restored tooth. However, there was no statistically significant difference among the tested groups.